Design and analysis of multistage transfer lines with interstage buffers - Özer, Serdar. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
Increasing importance of automation in manufacturing operations obliged the system designers to create large production systems that directly couple many stages of processing machinery. Since high capital investment is necessary to realize such large production systems, the investment has to produce to its full potential. However, little flexibility is the character of complex manufacturing systems. Break downs of single stations and other system imbalances cause idle periods for both machinery and manpower which leads to high financial loss (opportunity cost). Providing inventory banks between succcessive stages of the production line in order to decouple the stages and partially isolate overall system output from machine failures in any stage is one way of improving the line efficiency. This study is concerned in modeling and analyzing multistage automatic transfer lines with finite inter stage buffers. In the first part of the study an analytical model making use of the Markov chain approach is introduced. In tlie second part a simulation model of the multistage transfer line is pioposed. The aim is to establish relationships between system parameters like failure and repair rates of the stages and storage capacities and the important system performance measures like production rate, average in-process inventories and forced-down times. At the end of the work the applications of the theoretical results to the real world problems will be discussed.
Keywords: Markov processes.